Plant acclimation to environmental stress using priming agents - Filippou, Panagiota S.; Tanou, Georgia; Molassiotis, Athanassios; Fotopoulos, Vasileios (My University, 2013)
Several reports have provided increasing evidence that plants can be “conditioned” for more rapid or intense induction of defense responses leading to enhanced resistance to biotic and abiotic stresses (Beckers and Conrath 2007 ). An analogy therefore exists with the concept of vaccination in animals, where the administration of antigenic material results in the stimulation of adaptive immunity to a disease and the ultimate prevention or amelioration of the effects of infection by pathogens. The physiological state in which plants are able to activate defense responses faster, better, or both, is called the primed state of the plant. Priming may be initiated in response to an environmental cue that reliably indicates an increased probability of encountering a speci fi c stress factor, but a primed state may also persist as a residual effect following an initial exposure to the stress. The primed state can also be induced upon treatment with an acclimation-inducing agent, such as natural or synthetic compounds, as well as by colonization of plant tissues with bene fi cial microorganisms such as bacteria and arbuscular-mycorrhizal (AM) fungi. Under conditions of stress pressure, primed plants exhibit a higher fi tness than non-primed plants or defense-expressing plants. Although priming has been known to occur in plants for several decades, most progress in the understanding of this phenomenon has been made over the past few years. The present chapter represents an up-to-date overview of the literature in terms of some of the main priming agents commonly employed toward induced acclimation of plants to environmental challenges. These include nitric oxide (NO), hydrogen peroxide (H 2 O 2 ), hydrogen sul fi de (H 2 S), polyamines and bene fi cial microorganisms. However, it should be pointed out that several more priming agents exist and are successfully employed toward induced acclimation of plants to environmental stress, including the quaternary amine glycine betaine and b -aminobutyric acid. Some of the key research carried out with the use of the speci fi c priming agents under examination are summarized in Table 1.1 .
Keywords: Plants; Vaccination